Optimization Expression and Stability Test of Recombinant Human Interferon Alfa 2a Fusion Protein in Escherichia coli BL21 (DE3) - Santoso, Adi; Kusumawati, Arizah (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2015)
The rhIFN Î±2a is expressed as a fusion protein containing thioredoxine and polyhistidine sites at its N terminal. Our previous research has obtained recombinant human IFN Î±2a (rhIFN Î±2a) protein that expressed predominantly as a soluble form in E. coli BL21(DE3). Through systematic approach of various culture conditions, the aim of current this research is to acquire the best condition and its stability of recombinant rhIFN Î±2a fusion protein in a culture under study. Expression optimization performed by using three parameters, i.e.: temperature, induction time and inducer concentration. Various IPTG concentrations are 0.25 mM, 0.5 mM, 0.75 mM and 1.0 mM. The incubation time of bacterial cell culture carried out in 3, 4, and 5 hours at temperature 28, 30, and 37Â°C. The best condition was used to analyze the stability of rhIFN Î±2a protein expression up to ten generation. The expressed protein was analyzed using SDS PAGE and CBB staining. The optimal culture condition was found to be 37Â°C temperature with 4 hours time of induction and 1 mM IPTG concentration. Stability analysis revealed that the rhFN Î±2a protein expression remained stable until the tenth generation with molecular weight, approximately, 36 kDa.